S52 Clinical Effectiveness of Telemonitoring For Chronic Obstructive Pulmonary Disease (COPD): Randomised Controlled Trial. (19th November 2012) - Pinnock, H; McCloughlan, L; Todd, A; Hanley, J; Lewis, S; Krishan, A; MacNee, W; Pagliari, C; Sheikh, A; McKinstry, B
Abstract : Introduction: Previous trials of telehealthcare for COPD have included enhanced clinical care compared with controls. It is therefore unclear if telehealthcare alone improves clinical outcomes and reduces hospital admissions. Aim: To determine if telemetrically supported self-monitoring of COPD postpones hospital admissions when both intervention and control groups receive optimised care. Trial design: 1-year, researcher-blind RCT in UK primary care. Methods: Patients with a COPD admission in the previous year were randomised centrally to telemetric or traditional modes of monitoring: both groups received the same clinical care. The primary outcome, assessed by a researcher blinded to allocation, was time to first hospital admission caused by a COPD exacerbation over the trial year. Other outcomes included number of admissions, bed days, deaths and health-related quality of life (St George's Respiratory Questionnaire (SGRQ)). Results: We randomised 256 patients (128 telemonitoring): baseline characteristics were similar. Using an intention-to-treat analysis, there was no difference in time to admission between the groups (adjusted hazard ratio for admission (reference=tele-group) 1.03 (95%CI 0.70 to 1.50). 61 patients in each group had an admission. There was no significant difference in the mean number of admissions/person (tele-group: 1.2 (SD 1.9), control: 1.1 (SD 1.6) p=0.51); bed days (tele-group: 9.4 (SD 19.1) vs control 8.8 (SD 15.9) p=0.66); or deaths (tele-group: 16, control 21. p=0.38). Quality of life at 1 year was similar in both groups (SGRQ tele-group: 68.2 (16.3) vs usual: 67.3 (17.3), mean difference: 1.5 (95% CI –1.5 to 4.5)). Conclusion: When both groups received optimised care, telemonitoring did not appear to reduce the time to a hospital admission, duration of hospital admissions or increase quality of life. The place of telemonitoring in clinical care may depend upon whether it offers efficiency savings by enabling professionals to monitor and support the care of more patients than using traditional means of communication. ISRCTN number: 96634935 Funding: Chief Scientist Office of Scottish Government.